Guía para la determinación de procedimientos en las declaraciones del Impuesto a la Renta y el IMpuesto al Valor Agregado, de las personas naturales obligadas y no obligadas a llevar contabilidad, en el Ecuador - Valarezo Arellano, Evelyn Carolina (2016)
The present work is to provide the required individuals and not required to take accounting, a Tax Guide that allows them to easily determine your monthly income and expenses for the declaration and payment of Value Added Tax; and identify the tax base on which the state income tax, selecting the needed information to support statements, avoiding future penalties for breaching them and in turn fostered a culture tax help to taxpayers progressive development of our country. The methodology was first designed to determine the current legal tax obligations and then confirmed with field data, all the disadvantages faced by individuals to fully comply with the tax return and payment of VAT and IR. Among the results, the most important noted that 71 % of individuals who are either required or not required to maintain accounting records, said they did not have sufficient knowledge or advice on how to make their statements, adding that it is not the desire breach of these obligations, but do not know how to do; therefore 100% of individuals coincide in pointing out how advantageous it would be for them to have a Tax Guide to guide them with practical examples for each case, to the realization of their VAT returns and IR, in a way clear, easy and timely obtaining one hand the legal fulfillment of tax obligations and other welfare and tranquility in the taxpayer.